2013
DOI: 10.1089/jwh.2012.4107
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Other Disparities in Referral to Specialized Heart Failure Clinics Following Emergency Department Visits

Abstract: There are disparities in referral with respect to gender, age, and type of HF. These disparities in referral need to be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 32 publications
(37 reference statements)
1
45
0
Order By: Relevance
“…Within the field of cardiovascular medicine, Feldman et al 15 have shown that women with congestive heart failure are less likely to receive specialty heart failure care than do men. In both the inpatient and outpatient settings, women with coronary artery disease receive less aggressive care than do their male counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Within the field of cardiovascular medicine, Feldman et al 15 have shown that women with congestive heart failure are less likely to receive specialty heart failure care than do men. In both the inpatient and outpatient settings, women with coronary artery disease receive less aggressive care than do their male counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Women with symptoms of coronary heart disease are not treated as aggressively as males (Feldman et al . 2013). Although prevalence of arthritis is greater in women than men, and women are affected with greater severity, women are not offered the same treatment options as men (Godfrey and Nelson 2008).…”
Section: Literature Review: Ageism Sexism Older Women and Physiciansmentioning
confidence: 99%
“… 6 Female congestive heart failure patients are less likely to be treated by a heart failure specialist than men with the same illness. 7 In a recent, large study of Medicare beneficiaries, we found differences in AF treatment according to race and sex, including pharmacologic and nonpharmacologic modalities. 8 To investigate whether similar disparities exist in the use of catheter ablation for symptomatic AF in patients across multiple insurance types, we compared the demographic characteristics of patients of who did or did not undergo catheter ablation after presentation to the hospital with AF.…”
mentioning
confidence: 93%